If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying -1x^{2}+ 15x + -50 = 0 Reorder the terms: -50 + 15x + -1x^{2}= 0 Solving -50 + 15x + -1x^{2}= 0 Solving for variable 'x'. Factor a trinomial. (-10 + x)(5 + -1x) = 0## Subproblem 1

Set the factor '(-10 + x)' equal to zero and attempt to solve: Simplifying -10 + x = 0 Solving -10 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + x = 0 + 10 x = 0 + 10 Combine like terms: 0 + 10 = 10 x = 10 Simplifying x = 10## Subproblem 2

Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5## Solution

x = {10, 5}

| 7=m*17+b | | -4(y-3)+6=2(2y-2)+5y+8 | | 5y=1+10x | | 3(10-7x)=72 | | 0.6x=53 | | 5(-10+4x)=170 | | -2(-3-4x)=86 | | 6x+30=14x+2 | | 6x+30=14x-42 | | 2w+3W-16=(W+2) | | 3(-6x+7)=3 | | -4x-2=-12 | | 2x+31=12x-79 | | 4x+8=-24 | | 2x+12=64-6x | | 14-10x=88-24x | | 93-5x=7-10x | | 3x+1=7x-5 | | 6=3(y-2)-6y | | -4x+2=-30 | | 5x+10=-80-10x | | (5t)(-8)= | | 0.2-x=0.8x+2 | | (2x+3)(2x^2-4x-3)= | | x(x+6)-9=x(x-1)+1 | | -4x-2=12 | | -3+2-2= | | 4+8y=-24 | | 5x-4=90 | | -6x+5=1 | | 3x^2-7x-9=0 | | -y^2+x-8y-15=0 | | 2n^2-6n=28 | | 2+8x=12-2x | | 4x*2=36 | | 6(x+7)=-17(-x+4) | | 40000=23000*x^5 | | 20x^2+37x-3=-18 | | B^2w^2-1= | | 4=0.4[3d-5] | | x^3-7X^2+15x-15=0 | | Y=x^2-19x+90 | | 8(x+2)=6x+36 | | x^3-7X^2+11x-15=0 | | 12x^2+29x-3=-18 | | 20x=4x^2+25 | | 0=x^2-9x+12 | | -4z=40 | | -5=x+4 | | -5x=2x^2+6 | | [2+(16-13)*2]= | | 0=x^2+11x+28 | | 9n=8n+19 | | x(x-3)(2x+9)=0 | | 3a-12a+12=0 | | 2(2x-3)-(x+4)=4(x+3) | | Y=14 | | -4y+9=-3(2y+1) | | 2(x-5)-3(5-x)=10 | | 0.80x+0.35(160)=0.40(52) | | 3x-6+7x-6=x+9+2x+7 | | 6x^2+13=6x^2 | | 9x=4x+3(x-6) | | 3x(x+4)-2x+6=3x+2-4(x+3) | | 7x^2+13=6x^2 |